Kinetics research on three styles of track start in swimming - Zhao, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Swimming competition is becoming more competitive each year. Split second victory at the highest level of competitions happens more often than before. However, some factors remain unchanged. For instance, five parts including start, midway stroke, turn, final race, and touch pad make up the whole technique of an individual swimming event. It is, therefore, important to analyse each integral part and to explore the mechanism of the working elements. As the initial point of event, the technique of start underwent a series of changes from Swing style, and then Grab style to the latest Track Style. The advantage of the latest Track style is apparent in its steadiness, quick take off, and high horizontal speed. These elements are helpful to the fulfilment of the whole technique and this is why most of sophisticated swimmers choose to adopt a Track Start as their first choice. Methods It is unclear that what specific effect could be produced with the help of the new model platform. To answer this question, we duplicated a simple replica of the latest model and tested 8 male college swimmers with Track Start training for an adaptive training of 6 weeks. Three unique techniques were selected, named as Back-swing on big platform (BBP), Forward Leaning on big platform (FBP), and Back-swing on small platform (BSP). Camera data for swimmers were assorted and analysed. Evaluated comparisons were made on swimmers` kinetics in different phases of the event: set preparatory stage, set-off stage, flight phase, diving moment and then the phase of the underwater-slide. Meanwhile, document consultation and expert interviews were performed to the benefit of the research. Results The results of the present study suggest: 1. The BBP style enjoys the best steadiness, with its significant effect brought by active involvement of the arms. 2. BSP and BBP have the advantage of less delay from the off-platform which assists in providing a more rapid set-off. 3. Both off-platform angle and diving angle of the BBP and BSP are smaller in degree than that of FBP. In addition, the Centre of Gravity at the moment of diving and set-off as well as horizontal speed for BSP and BBP show the significant superiority than that of FBP. 4. As to the time consumed in the underwater-slide of 5m and 7m respectively, the styles of BBP and FSP hold the substantial advantage over that of BSP. 5. The style of BBP did not show its supremacy until the swimmers` underwater-slide reached 10m. BBP start technique is of absolute advantage and BBP can make full execution of its advantageous technique.